Impact of Dynamic PHEV load on Photovoltaic System - F.R. Islam; H. R. Pota (Institute of Advanced Engineering and Science, 2012)
This paper presents the dynamics of photovoltaic (PV) cell with Plug in Hybrid Electric Vehicles (PHEVs) load. It is expected that PHEVs are going to be charged during the day with solar PV energy sources at the parking sites of PHEVs. The present work offers a complete system for charging PHEVs with PV cell where PHEVs load are modelled based on third order battery model. System dynamics are analyzed at maximum power point while Perturb and Observe (P&O) method is used to ensure the tracking of maximum power point from the PV cell. This paper analyses the impact of PHEV loads on the dynamic behaviour of a solar power system under both small disturbance and large change in radiation. Simulation results demonstrate that it is important to consider the dynamics of PHEVs load for charging with PV cell.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1239